contestada

If f(x) = 3x + 10x and g(x) = 2x - 4, find (f- g)(x).
O A. 15x-4
B. 3X + 8x+4
O c. 3* – 8x+4
D. 3% + 12x-4

If fx 3x 10x and gx 2x 4 find f gx O A 15x4 B 3X 8x4 O c 3 8x4 D 3 12x4 class=

Respuesta :

Space

Answer:

B. 3ˣ + 8x + 4

General Formulas and Concepts:

Pre-Algebra

  • Distributive Property

Algebra I

  • Terms/Coefficients
  • Functions
  • Function Notation

Step-by-step explanation:

Step 1: Define

Identify

f(x) = 3ˣ + 10x

g(x) = 2x - 4

Step 2: Find

  1. Substitute in function values:                                                                          (f - g)(x) = 3ˣ + 10x - (2x - 4)
  2. [Distributive Property] Distribute negative:                                                    (f - g)(x) = 3ˣ + 10x - 2x + 4
  3. Combine like terms:                                                                                         (f - g)(x) = 3ˣ + 8x + 4

Answer:

3^x+8x+4

Step-by-step explanation:

f(x) = 3^x + 10x

g(x) = 2x - 4

(f- g)(x)=3^x + 10x  - (2x - 4)

Distribute the minus sign

(f- g)(x)=3^x + 10x  - 2x + 4

Combine like terms

         3^x+8x+4